PENGOLAHAN LIMBAH CAIR INDUSTRI JAMU DAN FARMASI MENGGUNAKAN ANAEROBIC BAFFLED REACTOR SECARA SHOCK LOADING DALAM UPAYA MENGHASILKAN BIOGAS - Fachry Amin N; Afifah Darda N.I.; Indro Sumantri (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2013)
PT. Sidomuncul is one of the factories that produce waste. Wastewatergenerated at 130m3 per day. Because of the big amount of wastewater produced, it is necessary to accommodate a short in time wastewater processing, that won’t required a large area and much time. Wastewater processing results of PT. Sidomuncul has a COD value of about 15000 mg /l. Wastes with high levels of COD is well treatedby anaerobically better than aerobic. Anaerobic wastewater treatment can be done if the value of minimal COD is 1500mg /l. This research will try to process the wastewater anaerobically by shockloading method using activated sludge. The purpose of this study was to determine the activated sludgestability when it is done with shock loading method and also the effect of COD level and biogas production as changed variables such rector design, HRT, activated sludge type, and activated sludge height. Observed responses are pH effluent, COD levels, and gas production. The results of this research are the process of anaerobic wastewater shock loading on herbal medicine and pharmaceutical industry could reduce COD levels ranged from 78.46% to 93.97% and produce biogas at it’s best using organic fertilizer sludge with 1/3 height of ABR.